Till behavior and its relationship to active-layer hydrology, District of Keewatin, Northwest Territories - Dyke, Larry; Egginton, Paul (Canadian Geotechnical Journal, 1988)
Well-graded tills are a common surficial material over much of the Canadian Arctic from northern Manitoba to Somerset Island. The compactibility and bearing strength of these tills when thawed appear to be controlled by groundwater flow in the active layer. Water seeping from bedrock outcrops flanked by till enters the till active layer and flows via macropores formed as ice lenses thaw. This flow appears to retard consolidation of the till. Slopes having no seepage source consolidate more rapidly. This seepage maintains the till in a state highly susceptible to liquefaction and would yield material with a moisture–density condition unsuitable for construction use. Key words: till, surficial, compactibility, bearing capacity, groundwater, seepage, freeze–thaw, liquefaction.